Personalized Visualization of the Gestures of Parkinson’s Disease Patients with Virtual Reality - Konstantinos Sakkas; Eirini Georgia Dimitriou; Niki Eleni Ntagka; Nikolaos Giannakeas; Konstantinos Kalafatakis; Alexandros T. Tzallas; Evripidis Glavas (Future Internet)
Parkinson’s disease is a neurological disorder characterized by motor and non-motor symptoms. Assessment methods, despite the many years of existence of the disease, lack individualized visualization. On the other hand, virtual reality promises immersion and realism. In this paper, we develop an integrated system for visualizing the gestures of Parkinson’s disease patients in a virtual reality environment. With this application, clinicians will have information about the unique motor patterns and challenges they must address in each individual patient’s case, while the collected data can travel and be easily and instantly visualized in any location. At the beginning of this research, the current terms of immersive technologies in conjunction with data visualization and Parkinson’s disease are described. Through an extensive systematic literature review, the technological developments in the field of Parkinson’s data visualization are presented. The findings of the review lead to the experimental procedure and implementation of the application. The conclusions drawn from this work fuel future extensions on the contribution of immersive technologies to various diseases.